Alternate wetting and drying and nitrogen fertilizations under different soil conditions alter carbohydrate and nitrogen metabolisms in rice - Kyoung Rok Geem; Gahyun Kim; Jwakyung Sung (Applied Biological Chemistry)
Abstract Rice (Oryza sativa L.), a key staple crop, contributes over 20% of the daily caloric intake for more than 3.5 billion people worldwide. The continuous growth of the global population necessitates a steady increase in rice production, promoting advancement in agricultural cultivation systems to achieve both sustainability and productivity. Effective water and nitrogen (N) fertilizer management are crucial for optimizing rice productivity and ensuring environmental sustainability. This study investigates the interactive effects of alternate wetting and drying (AWD) irrigation and different nitrogen sources under contrasting soil conditions, focusing on nitrogen use efficiency (NUE), nitrogen metabolism, and carbohydrate metabolism. Our findings showed that soil type significantly influenced NUE and N metabolism depending on nitrogen fertilizers more than water management under ALN. However, under AHN, both nitrogen fertilizers and water management affected NUE and nitrogen metabolism. In acidic, low-nutrient soils (ALN), AWD decreased nitrogen uptake efficiency and downregulated the nitrogen transport and assimilation-related genes. Conversely, in alkaline, high-nutrient soils (AHN), AWD enhanced nitrogen uptake and assimilation, leading to increased upregulation of nitrogen transporter and assimilation genes. Additionally, AWD altered carbohydrate metabolism, increasing or decreasing carbohydrates accumulation by soil chemical and nutrient conditions. This study provides valuable insights into improving rice productivity by optimizing nitrogen use efficiency and promoting sustainability under various soil and water conditions.